Pulse radiolysis of carboxylic acids used as ligands of metal oxide nanocluster resists. (23rd August 2019) - Yamada, Teppei; Muroya, Yusa; Yamashita, Shinichi; Komuro, Yoshitaka; Kawana, Daisuke; Yamazaki, Akiyoshi; Kozawa, Takahiro
Abstract: The radiation-induced reactions of ligands play an important role in the sensitization of metal oxide nanocluster resists. However, the details in the radiation chemistry of ligands for metal oxide nanocluster resists are still unknown. In this study, the radiation-induced reactions of carboxylic acid ligands were investigated using a pulse radiolysis method. The rate constants for the reactions of molecular and ionic forms of tiglic, angelic, o -toluic, and p -toluic acids with hydrated electrons were determined. The rate constants for the reactions of tiglic, angelic, benzoic, o -toluic, and p -toluic acids with dodecane radical cations were also determined. The radical ions of tiglic and angelic acids were more unstable than those of benzoic, o -toluic, and p -toluic acids. The results obtained in this study indicate that the molecular structures of ligands affect their reactivity to cationic and anion species and the stability of their radical cations and anions.